Geo-tiles: manufacturing tiles from copper mine tailings using geopolymerisation - Makole, Karabo (Department of Civil Engineering, 2025)
Sustainability in ceramic tile manufacturing is constrained both by the substantial energy required to power the high temperature production process (>950°C) and its reliance on virgin raw material from natural reserves. Conventional solutions to manage the voluminous residue of the mining industry are also unsustainable as they do not comprehensively eliminate the hazards posed. This study investigated the technical feasibility of using aluminosilicate-rich mine waste, termed tailings, as the primary raw material to produce tiles using the low-energy geopolymerisation process. Traditional efforts to increase sustainability of ceramic tile manufacturing include waste valorisation to reduce virgin raw material consumption and optimisation of the manufacturing process to reduce energy demand. Despite adoption of best available techniques, the high temperatures required render the process energy intensive. Promising research is underway to produce tiles using the low-energy biomimetic processes of microbially induced calcite precipitation. An ecological limitation of and key improvement recommendation for this technique is to increase the quantity of waste material it repurposes as feedstock. Geopolymerisation presents a promising path to redress the ecological limitations of tile manufacturing as it both operates at low temperature (<210°C) and can utilise a feedstock comprising waste. The geopolymerisation reaction generally entails a fine-grained substance comprising reactive aluminosilicates being mixed with a high pH solution (the alkali activator). After mixing and being subjected to elevated temperatures (23°C – 210°C), the aluminosilicates dissolve and recombine into a gel that binds the non-reactive particles into a gel matrix called a geopolymer. Prior attempts at fabricating tiles by geopolymerisation have not simultaneously combined a low energy process that fully incorporates waste as feedstock. The large volumes of particulate waste with inhomogeneous mineralogy produced by the mining industry are ideal for geopolymerisation. Consisting of a combination of fine dust particles and residual processing fluid, mine tailings contribute to negative externalities affecting both atmospheric and terrestrial environments, in addition to endangering human life. Traditional tailings risk mitigation techniques often demand indefinite oversight, and do not completely eliminate hazards. The most comprehensive solution is to repurpose the entire volume of tailings as raw material for economically viable alternative uses or products. It was thus hypothesised that the sustainability of both the mining and ceramic tile industries could be ameliorated by valorising mine tailings as feedstock for production of geopolymerised tiles, referred to as geo- tiles in this study. This thesis investigated the technical feasibility of geo-tile production using copper (Cu) mine tailings as they accounted for the largest share of tailings generated globally (46% in 2016). The alkali activator solution they were mixed with was concentrated (15 M) aqueous sodium hydroxide. A custom stainless-steel mould was fabricated, and a novel manufacturing procedure developed to form and compress the moistened tailings into 100 mm × 100 mm × 10 mm geo- tiles. Geo-tiles were then benchmarked against standard certification criteria to validate performance relative to conventional tiles. Technical feasibility was assessed using mechanical strength parameters and tile testing techniques obtained from international, South African and American standard accreditation bodies. The primary mechanical strength parameter investigated was modulus of rupture (MOR), which depends on the tile's breaking strength. Water absorption test results needed to fall within a specified range to validate breaking strength and MOR targets. Additional quality assurance (QA) criteria of abrasion resistance and heavy metal encapsulation efficiency were investigated to indicate a further development direction should technical feasibility be established. Selecting a curing duration and temperature that minimised the process' energy intensiveness was the first step. Curing at 85°C, 95°C and 105°C respectively required 7-day, 4-day and 2-day curing durations. The curing regime selected for subsequent geo-tiles produced was 105°C for two days because this required 34 MJ of electrical energy, less than the 58 MJ and 92 MJ consumed by the other two regimes. Literature indicated that input factors with the potential to maximise mechanical strength of tailings-based geopolymers were forming pressure and particle size. The first of these variables was investigated by varying the pressure applied by a hydraulic press that shaped the moist geo-tiles between 0.1 MPa, 0.2 MPa, 0.3 MPa and 0.4 MPa for different tiles. To investigate the second variable, five batches of Cu tailings were prepared, each containing progressively larger proportions of fine material. This was achieved by passing each batch through one of five sieves: 150 μm, 212 μm, 300 μm, 425 μm and 600 μm. The sieve aperture size through which a given batch of tailings was passed defined the particle size distribution (PSD) classification of that batch. Thus, the batch that passed through the 600 μm sieve was assigned a PSD classification of 600 μm, the batch that passed through the 425 μm sieve was assigned a PSD classification of 425 μm and so on. The ranges of forming pressure and PSD classification selected were based on cylinders and cubes from literature. Since tiles have a differing form factor, the validity of forming geo-tiles over these inferred input factor ranges needed verification. Response surface methodology (RSM) achieved this, whilst also giving preliminary insights into how the two input predictor factors influenced the response variable (MOR). The RSM model validated the design space by indicating that geo-tiles had adequate strength over the entire design space. The RSM model also indicated that using finer grained tailings (reducing PSD classification) had a larger effect on increasing MOR than modifying forming pressure. This was quantified by the Pearson's correlation coefficient, which was −0.77 for PSD vs MOR whereas it was −0.06 for forming pressure vs MOR. The highly negative correlation between PSD and MOR aligns with literature. Finer grained tailings have a larger specific surface area, increasing the region upon which the geopolymerisation reaction can proceed, ultimately enhancing mechanical strength. A likely explanation for the low correlation between forming pressure and MOR was that prior to curing, the geo-tiles were too moist, with a solid to liquid ratio (SLR) between 4.3 and 4.7. When forming pressure variation significantly influenced mechanical strength, geopolymers with much stiffer rheology were used. Literature reports that such geopolymers were formed under similar conditions to geo-tiles but were characterised by SLRs ≈ 5.5 – 5.6. A design chart was developed to evaluate the breaking strength and MOR results for geo-tiles against limits dictated by International Organization for Standardization (ISO13006 (2018)) and South African National Standards (SANS1449 (2012)). The chart indicates a target performance region requiring breaking strengths >800 N and MOR results >16 MPa. Geo-tiles with the highest MOR were formed at 0.1 MPa pressure, using Cu tailings that had passed through a 150 μm sieve, i.e. had a PSD classification of 150 μm. The breaking strength and MOR of the geo-tile formed under these conditions were respectively 986 ± 151 N and 18.5 ± 0.7 MPa; exceeding the design chart limits. Water absorption of geo-tiles needed to fall within 6% and 11% for these targets to be valid. This QA condition was met as results ranged between 6.4% and 9.8%. Since it classifies flooring use cases, abrasion was used as the second QA criterion. Equipment constraints necessitated adoption of American Society for Testing and Materials (ASTM C418) standards to evaluate abrasion resistance. Of the classifications governed by the ASTM C418 equipment, the abrasion limits for interlocking paving units (IPUs) represent the most abrasively demanding service conditions. Selection of IPU requirements as the QA benchmark for geo-tiles was made under the assumption that meeting the most stringent abrasion targets would indicate suitability for less severe situations. Requirements for IPUs only allow 0.3 cm3/cm2 of volumetric abrasion loss, with a maximum allowable abrasive depth of 3 mm. Both requirements were met as the volumetric abrasion of geo-tiles with the highest MOR was 0.11 ± 0.01 cm3/cm2 with an abrasive depth of 1.1 ± 0.1 mm. These results suggest geo-tile applications could include domestic floors and patios as well as residential sidewalks and driveways. As with abrasion, equipment limitations necessitated a heavy metal test that exposed geo-tiles to conditions more severe than required for typical service conditions and standardised tests for tiles. Geopolymerisation of Cu tailings to form geo-tiles reduced leaching in 16 of the 17 heavy metals detected by X-ray fluorescence and inductively coupled plasma mass spectrometry analyses. However, encapsulation of heavy metals in geo-tiles occurred at lower efficiencies (≤37%) than those achieved by geopolymers in literature (>90%). Therefore, the final QA criterion pertaining to heavy metal encapsulation was not met. The likely cause of incomplete encapsulation was that the Si/Al ratio of the source Cu tailings (4.5) was higher than typically required for effectively complete heavy metal immobilisation (Si/Al ≈ 2). Concerningly, the 17th heavy metal detected, Hg, leached more after undergoing geopolymerisation. Relativistic effects inherent to Hg that affect its bonding behaviour were the most likely explanation, in addition to Hg's inability to form low solubility hydroxide solids, precluding its encapsulation using alkali cementation-based methods like geopolymerisation. Investigation of additives that can both reduce the Si/Al ratio of the tailings and promote encapsulation of Hg was recommended. One that has achieved the former is NaAlO2, whilst suggestions to address the latter from literature include Ca and Na2S. Additional considerations include observations by both scanning electron micrograph and energy dispersive spectroscopy indicating that geo-tiles comprised sodium aluminosilicate hydrate geopolymeric gel. Furthermore, the embodied specific energy of geo-tiles (10.86 kWh/m2) is lower than that for both porcelain (26.6 kWh/m2) and cement tiles (16.6 kWh/m2). Finally, decorative options operating below 950°C are required to prevent the geo-tiles melting. Overall, this dissertation shows that geopolymerisation of Cu mine tailings to produce tiles is technically feasible. Geo-tiles exceeded standards-based targets for breaking strength and MOR whilst meeting abrasion and water absorption QA criteria. Geo-tile production valorises harmful mining waste as a primary feedstock and respectively uses 59% and 35% less embodied energy than required to make conventional porcelain and cement tiles. Whilst heavy metal leaching criteria was not met, there is strong literature support that additives can significantly improve encapsulation efficiencies. Combining additives with standard testing that is both appropriately aggressive and representative of service conditions increases the likelihood of meeting the heavy metal benchmark. It is therefore suggested that geo-tiles be tested in compliance with the ISO standards outside the scope of this study, in addition to undertaking of an economic feasibility study to evaluate scalability beyond lab production.